Thin film solar cell P-type intermediate layer and preparation method thereof

The CuCo2O4 film was prepared as the intermediate layer of CZTSSe solar cells by sol-gel method, which solved the problems of low back interface quality and high cost, improved the photoelectric conversion efficiency of the solar cell and reduced the series resistance.

CN119133277APending Publication Date: 2024-12-13ORDOS INST OF APPLIED TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411147507.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The photoelectric conversion efficiency of CZTSSe solar cells is limited by a large open circuit voltage loss and a low fill factor, mainly due to the low-quality back electrode interface, the high preparation cost of existing intermediate layer materials and the increased series resistance.

Method used

The p-type CuCo2O4 film with an amorphous structure was prepared by sol-gel method as the intermediate layer of the back interface of CZTSSe solar cell. The mixed solution was prepared by organic acid salts of Co and Cu or its crystalline hydrocarbons and applied and heat-treated to obtain high light transmittance. and wide bandgap CuCo2O4 layer.

Benefits of technology

Effectively reduce back interface carrier recombination, improve the quality of the absorption layer, improve the photoelectric conversion efficiency of CZTSSe solar cells, and is low in cost and does not increase series resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133277A_ABST
    Figure CN119133277A_ABST
Patent Text Reader

Abstract

According to the thin-film solar cell P-type intermediate layer, the P-type intermediate layer is an amorphous CuCo2O4 layer, the P-type intermediate layer is arranged between a back electrode of a solar cell and a CZTSSe thin film layer, and the CuCo2O4 layer has the light transmittance of not less than 60% and the band gap value of not less than 1.5 eV at the light wavelength band of 400-1000 nm. The CuCo2O4 middle layer is prepared through a simple sol-gel method, the solar cell obtained through the CuCo2O4 middle layer has high photoelectric conversion efficiency, bidirectional improvement of a CZTSSe absorption layer and a back electrode interface is achieved, and the performance of a cell device is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of solar cell materials, and in particular to a thin-film solar cell P-type intermediate layer and a preparation method thereof. Background Art

[0002] Kesterite-structured copper zinc tin sulfur selenide (Cu2ZnSn(S,Se)4, CZTSSe) has an adjustable band gap and a high optical absorption coefficient (greater than 10 4 cm -1 ), good stability and abundant raw material sources, it is expected to become one of the new generation of solar cells with the greatest industrial potential. Recently, the photoelectric conversion efficiency of CZTSSe solar cells has reached 14.9%, but it is still far lower than the SQ theoretical limit efficiency (33%) and the highest efficiency of the same type of CIGS (23.64%). Large open circuit voltage loss and low fill factor are the main reasons that restrict further improvement of its photoelectric conversion efficiency, so related research needs to be further carried out.

[0003] The low-quality back electrode interface is one of the factors that lead to large open circuit voltage loss and low fill factor, which is mainly due to the high recombination probability of photogenerated carriers at the back interface. Therefore, in order to reduce the back interface recombination and thus improve the battery performance, it is particularly important to optimize the back interface quality. Researchers have improved the back interface quality and the crystal quality of the absorption layer by introducing an intermediate layer at the junction of CZTSSe and Mo. CuAlO2 film, intermediate layers such as TiN, Al2O3, ZnO, etc. have also been reported to be used to improve the back interface quality. Although the introduction of these intermediate layers will improve the photoelectric conversion efficiency of the battery device, it will also bring negative problems such as increased series resistance. In addition, most of the above-mentioned intermediate layers are prepared using expensive sputtering equipment, which increases the cost. Summary of the invention

[0004] To solve the above problems, the present invention provides a method for preparing an amorphous p-type CuCo2O4 thin film (the layer is composed of oxides containing Cu and Co and Cu(OH)2, and is referred to as CuCo2O4 thin film in this patent for convenience) by a low-cost sol-gel method as an intermediate layer of the back interface of a CZTSSe solar cell, and an amorphous p-type CuCo2O4 thin film obtained by the method. Specifically, the technical solution of the present invention is as follows:

[0005] The first part of the present invention provides a P-type intermediate layer of a thin-film solar cell, wherein the P-type intermediate layer is a non-crystalline CuCo2O4 layer, and the P-type intermediate layer is arranged between the back electrode and the CZTSSe thin film layer of the solar cell, and the CuCo2O4 layer has a light transmittance of not less than 60% in the 400-1000nm light wavelength band, and has a band gap value of not less than 1.5eV, preferably, a band gap value of not less than 1.75ev.

[0006] In the present invention, the CuCo2O4 layer has a light transmittance of not less than 70% in the 400-1000nm optical wavelength band, preferably, a light transmittance of not less than 80%, and in particular, a light transmittance of not less than 90%. Preferably, the CuCo2O4 layer has a light transmittance of not less than 70% in the 600-1000nm optical wavelength band, preferably, a light transmittance of not less than 80%, and in particular, a light transmittance of not less than 90%. More preferably, the CuCo2O4 layer has a light transmittance of not less than 70% in the 800-1000nm optical wavelength band, preferably, a light transmittance of not less than 80%, and in particular, a light transmittance of not less than 90%, and more particularly, a light transmittance of not less than 95%.

[0007] The band gap value of the CuCo2O4 layer of the present invention is not less than 2eV. Preferably, the band gap value of the CuCo2O4 layer is not less than 3eV.

[0008] In the present invention, the thickness of the P-type intermediate layer is 10 to 100 nm, preferably, the thickness is 10 to 50 nm, and more preferably, the thickness is 15 to 20 nm.

[0009] The amorphous CuCo2O4 layer of the present invention is composed of a compound CuO x1 n1CoO x2 ·n2Cu(OH)2 composition, wherein x1 is 0.80-1.00, x2 is 1.20-1.50, n2 is 0.10-0.40, and n1 / (1+n2) is 1.90-2.10; preferably, x1 is 0.85-0.95, x2 is 1.30-1.40, n2 is 0.15-0.30, and n1 / (1+n2) is 1.90-2.00; more preferably, x1 is 0.90-0.95, x2 is 1.33-1.36, and n2 is 0.20-0.25.

[0010] In the present invention, the CuCo2O4 intermediate layer is a thin film prepared by solution coating. Specifically, the CuCo2O4 intermediate layer is obtained by coating a mixed solution prepared from organic acid salts of Co and Cu or their crystalline water compounds, wherein the molar ratio of Co to Cu in the mixed solution is 1.9 to 2.1:1, and the concentration of the mixed solution is 0.1 to 0.5 M. In the present invention, the solvent of the mixed solution is an organic polar solvent selected from solvents including ethers, alcohols, and ketones, in particular monoethers and polyethers. In a specific embodiment of the present invention, ethylene glycol monomethyl ether is used as the solvent.

[0011] In a preferred technical solution of the present invention, the CuCo2O4 intermediate layer is obtained by single-layer coating by solution method. The CuCo2O4 intermediate layer is obtained by coating a mixed aqueous solution prepared from organic acid salts of Co and Cu or their crystalline water compounds and then further heat-treating the mixed aqueous solution, wherein the heat-treating temperature is 200-250°C and the heat-treating time is 10 minutes.

[0012] The second part of the present invention is to provide an application of the P-type intermediate layer of the thin-film solar cell in the preparation of a solar thin-film cell.

[0013] The third part of the present invention is to provide a method for preparing a solar thin film battery comprising the P-type intermediate layer, comprising the following steps:

[0014] Step 1. Solution preparation and treatment, including preparing a mixed solution from organic acid salts of Co and Cu or their crystalline water compounds, wherein the molar ratio of Co to Cu in the mixed solution is 1.94:1 and the concentration of the mixed solution is 0.3M;

[0015] Step 2. Preparation and treatment of the back electrode, including using soda-lime glass as a substrate and sputtering a Mo layer of about 800 nm thick on the substrate as the back electrode of the CZTSSe solar cell;

[0016] Step 3. Prepare a CZTSSe absorption layer film inserted into the CuCo2O4 layer, including applying the mixed solution obtained in step 1 on the Mo layer back electrode obtained in step 2 and performing heat treatment, the heat treatment temperature is 200-250°C, the heat treatment time is 10 minutes, to prepare a CuCo2O4 layer, then apply a CZTS precursor solution on the CuCo2O4 layer, and further perform selenization treatment to obtain a CZTSSe absorption layer film inserted into the CuCo2O4 layer;

[0017] Step 4. Prepare a solar cell, including depositing a cadmium sulfide (CdS) film of about 50 nm on the absorption layer film obtained in step 3 by a chemical water bath method, and further using a radio frequency magnetron sputtering method to deposit high-resistance intrinsic zinc oxide (i-ZnO) and low-resistance indium tin oxide (ITO) as window layers of the CZTSSe solar cell, and further using a thermal evaporation method to evaporate Ag on the surface of the film after the sputtering of the window layer as a top electrode to obtain a solar cell.

[0018] In the method of the present invention, in step 1, the crystalline water compound of the organic acid salt of Co and Cu is used to prepare a mixed solution, specifically, the mixed solution is prepared using Co(CH3COOH)2·4H2O and Cu(CH3COOH)2·H2O.

[0019] In the method of the present invention, the back electrode in step 2 includes a two-step deposition process of a bottom layer and a top layer, the thickness of the two Mo layers is about 400nm, a higher power is used when preparing the bottom Mo, and a lower power is used when preparing the top Mo. In the present invention, the higher power and the lower power are based on the sputtering power of the bottom Mo and the top Mo preparation, which are relatively higher and lower.

[0020] In the method of the present invention, in step 3, the CuCo2O4 layer is obtained by applying the mixed solution at least once and heat treating it. Specifically, after the CuCo2O4 layer is prepared by heat treating, the solution of step 1 is repeatedly applied on the CuCo2O4 layer and heat treated to prepare a multilayer CuCo2O4 layer. In the preferred technical solution of the present invention, the number of CuCo2O4 layers is 1, and the heat treatment temperature is 200°C. The mixed solution coating is to coat the mixed solvent at 0.05-0.5 mL / cm 2 The amount of coating is preferably 0.1-0.2 mL / cm 2 The coating is applied in an amount of , and heat treated after coating.

[0021] The CuCo2O4 film obtained by the present invention has the characteristics of high conductivity, strong hole transport ability, wide band gap and high optical transparency. The CuCo2O4 film of the present invention can effectively reduce the carrier recombination at the back interface as an intermediate layer and improve the quality of the absorption layer. When the number of spin-coated layers of the CuCo2O4 intermediate layer is 1 and the heat treatment temperature is 200°C, the photoelectric conversion efficiency of the CZTSSe solar cell is increased by 24.3% (the photoelectric conversion efficiency is increased from 6.95% to 8.65%). BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 (a)-(c) Cu2p of CuCo2O4 thin films prepared on soda-lime glass substrate at different heat treatment temperatures 3 / 2 and (d)-(f)Co2p3 / 2 XPS spectrum of

[0023] Figure 2 Hall electrical analysis of CuCo2O4 thin films prepared on soda-lime glass substrate at different heat treatment temperatures;

[0024] Figure 3 (a) Transmittance spectra and (b) (αhν) of CuCo2O4 films prepared on soda-lime glass substrate at different heat treatment temperatures 2 The relationship curve with hν;

[0025] Figure 4 (a) XRD patterns and (b) magnified images of (112) diffraction peaks of CZTSSe films on soda-lime glass / Mo substrate and soda-lime glass / Mo / CuCo2O4 (different number of CuCo2O4 spin-coated layers);

[0026] Figure 5 is the half-height width of the (112) diffraction peak of different samples;

[0027] Figure 6 Raman scattering spectra of CZTSSe thin films on soda-lime glass / Mo substrate and soda-lime glass / Mo / CuCo2O4 (different number of CuCo2O4 spin-coated layers);

[0028] Figure 7 JV curves of CZTSSe solar cell devices on soda-lime glass / Mo substrate and soda-lime glass / Mo / CuCo2O4 (with different number of CuCo2O4 spin-coated layers); DETAILED DESCRIPTION

[0029] 1. Pretreatment and preparation of mixed solution

[0030] Use detergent solution diluted with deionized water to ultrasonically clean the screw-mouth bottle for 10 minutes and twice, then rinse the bottle, bottle cap and gasket with high-pressure deionized water. Blow dry the cleaned screw-mouth bottle, bottle cap and gasket with a nitrogen gun to prevent dust and other particulate matter from contamination.

[0031] Weigh 2.235 mmol Co(CH3COOH)2·4H2O and 1.151 mmol Cu(CH3COOH)2·H2O using a high-precision analytical balance in an air atmosphere. Add 10 ml ethylene glycol methyl ether solution, stir at room temperature for 10 min, then use ultrasonic dispersion for 10 min, and stir at room temperature for another 10 min. Add 10 μL ethanolamine as a solution stabilizer, continue stirring for 2 h, and obtain a dark purple sol.

[0032] The obtained dark purple sol was placed in an air environment for aging for 24 hours. The aged dark purple sol was filtered using a polytetrafluoroethylene filter. The filtered sol was stored in a cleaned screw-mouth bottle and the bottle mouth was sealed with a sealant.

[0033] 2. Preparation of CuCo2O4 interlayer on glass substrate

[0034] Use a 1.1mm thick soda lime glass (SLG) substrate and cut it into 2*2cm size using a glass cutter. Put the cut soda lime glass sheet into a beaker, prepare and add a 20:1 deionized water: dishwashing liquid mixed solution, and heat it at 65°

[0035] Water bath for 2 hours; then scrub the soda-lime glass sheet and rinse it with deionized water, place the soda-lime glass sheet on a polytetrafluoroethylene rack and put it in a beaker with 300ml deionized water for ultrasonic cleaning, 3 times * 30min. Replace the newly prepared deionized water each time; then put the soda-lime glass sheet into a beaker containing a 1:1:1 solution of isopropanol: acetone: methanol, repeat the ultrasonic cleaning 3 times, 30min each time; then rinse the glass sheet with deionized water, and then put it into a beaker containing deionized water for ultrasonic cleaning, 3 times * 30min. Replace the newly prepared deionized water each time; then put the soda-lime glass sheet into a beaker containing anhydrous ethanol for ultrasonic cleaning for 30min; then place the soda-lime glass sheet in an oven for drying and preservation. Use ultraviolet ozone cleaning equipment to treat the soda-lime glass substrate for 15min to remove organic matter and unpaired chemical bonds on the substrate surface to increase the wettability of CuCo2O4 colloid on the substrate.

[0036] Use a dropper to evenly drop the filtered sol on the substrate (soda-lime glass) at a rate of 5 drops / 10s, spin-coat at a speed of 4000rpm, and drop and spin-coat for 30s. The spin-coated film samples were placed on a constant temperature heating table at 200℃, 250℃ and 300℃ in air for 10min to evaporate the solvent and remove the residual acetate organic matter. Repeat the spin coating with different spin coating numbers to achieve different film thicknesses. The CuCo2O4 film directly spin-coated on the soda-lime glass was placed on a constant temperature heating table at 200℃, 250℃ and 300℃ for 10min, and the prepared film samples were represented by CCO-20, CCO-25 and CCO-30 respectively. After testing, the thickness of the single layer of CuCo2O4 after heat treatment was 18nm.

[0037] Through XPS testing, Hall testing, and UV-visible spectrophotometer testing, it was determined that the thin film sample CCO-20 performed optimally in terms of element valence and content, electrical properties, and optical properties. The CCO-20 thin film sample was selected as the intermediate layer and assembled into the CZTSSe thin film solar cell.

[0038] 3. Preparation of CuCo2O4 interlayer on Mo back electrode and obtaining solar cell containing the interlayer

[0039] (1) Back electrode preparation and processing

[0040] A Mo layer about 800nm ​​thick was sputtered on a dried and cleaned soda-lime glass substrate by DC magnetron sputtering as the back electrode of the CZTSSe solar cell. Specifically, it includes a two-step deposition process of the bottom layer and the top layer. The thickness of the two layers of Mo is about 400nm. When the bottom layer of Mo is prepared, a higher power is used, which can be well deposited and adhered to the soda-lime glass substrate, thereby effectively preventing it from falling off during the preparation of other functional layers; when the top layer of Mo is prepared, a lower power is used, so that it has excellent conductivity, which helps to reduce the resistance of the back electrode and improve the transmission and collection capacity of hole carriers. The specific sputtering process parameters of the two layers of Mo are shown in Table 1.

[0041] Table 1. Mo sputtering process parameters

[0042]

[0043] (2) Preparation of CZTSSe absorber film inserted into CuCo2O4 layer

[0044] Take the screw-mouth glass bottle and rotor out of the aqua regia bucket and ultrasonically clean them with deionized water and anhydrous ethanol respectively, ensure that they are thoroughly cleaned and then dried for use. Weigh 1.1408g of Cu(CH3COOH)2·H2O and 0.8864g of SnCl2·2H2O powder and add them to the dried screw-mouth glass bottle in turn, then inject 5ml of DMSO solvent into the bottle via a syringe, seal the screw-mouth bottle with sealing glue and place it on a magnetic stirrer, and stir continuously for 12h at room temperature to obtain a light green solution. Weigh 0.5603g of ZnCl2 and add it to the screw-mouth bottle where stirring has stopped, seal it and continue stirring for about 1h until it is completely dissolved. Finally, add 1.6g of SC(NH2)2 to the bottle, seal it with sealing glue and continue stirring for 2h. The solution first turns black with slight heat, and finally turns light yellow as SC(NH2)2 dissolves. At this point, the copper zinc tin sulfur (CZTS) precursor solution was prepared, and the above process was carried out in air. The molybdenum (Mo)-plated substrate on the soda-lime glass was treated with an ultraviolet ozone cleaning device for 15 minutes to remove organic matter and unpaired chemical bonds on the substrate surface to increase the wettability of the CuCo2O4 colloid and the CZTS precursor solution on the substrate.

[0045] In a N2-filled glove box (water and oxygen are both less than 20ppm), the CZTS precursor solution prepared above is filtered with a polytetrafluoroethylene filter, and then the mixed solution in step 1 (i.e., the mixed solution of Co(CH3COOH)2·4H2O and Cu(CH3COOH)2·H2O prepared) is spin-coated on a Mo-plated substrate to prepare a CCO-20 film. The preparation process is consistent with the above. Subsequently, the CZTS precursor solution is evenly spin-coated on the CCO-20 film. The spin coater rotates at 3000rpm for 30s to evenly coat the precursor solution on the surface of the CCO-20 film. The spin-coated CZTS precursor film is placed on a heating table (the temperature is set to 430℃) for baking. After 3 minutes, the sample is removed and the spin coating is continued after it is naturally cooled. The above process is repeated 5 times to obtain a CZTS precursor film inserted into the CCO-20 film.

[0046] The prepared precursor film was placed in a graphite box containing Se particles, the N2 flow rate was adjusted to 80 sccm, the selenization program was set to rise from room temperature to 540°C in 1 minute, and kept warm for 20 minutes, and the selenization process was started by clicking Start. After the selenization was completed, the furnace was allowed to cool naturally to room temperature to obtain a CZTSSe absorption layer film inserted into the CCO-20 film.

[0047] (3) Preparation of solar cells

[0048] Cadmium sulfide (CdS) acts as a buffer layer in solar cells. A CdS film of about 50 nm is deposited on the surface of the CZTSSe absorption layer by a chemical bath method (CBD). The specific preparation process includes: placing a beaker containing 250 ml of deionized water on a stirring table at 500 rpm for continuous stirring. Then weigh 0.0768 g of cadmium sulfate powder with an electronic balance, add it to the beaker and stir for 5 minutes until the powder is completely dissolved. Then use a dropper to drip 12.5 ml of ammonia water and continue stirring for 5 minutes. After that, the polytetrafluoroethylene sample rack containing the CZTSSe sample is hung on the beaker, and the solution in the beaker completely covers the CZTSSe sample. Then add 0.11 g of thiourea to the solution and continue stirring for 5 minutes. After the stirring process is completed, the beaker is transferred to a water bath (the temperature is set to 70°C) for heating and stirring until the color of the film surface changes from grayish white to blue-purple. The film surface was rinsed with deionized water and anhydrous ethanol in turn and then placed in a drying oven at 60°C for drying.

[0049] Subsequently, high-resistance intrinsic zinc oxide (i-ZnO) and low-resistance indium tin oxide (ITO) were deposited as window layers of CZTSSe solar cells by radio frequency magnetron sputtering. The SLG / Mo / CCO-20 / CZTSSe / CdS sample was placed on a special mask and then placed in a magnetron sputtering chamber. Vacuuming, pre-sputtering and sputtering were performed in sequence to sputter i-ZnO (50nm thick) and ITO (200nm thick). The process parameters are shown in Table 2.

[0050] Table 2. Sputtering process parameters of i-ZnO and I TO window layers

[0051]

[0052] Ag was deposited on the surface of the sputtered window layer by thermal evaporation as the top electrode with a thickness of 100 nm. Finally, the sample was mechanically scribed into 9 lines with an effective area of ​​0.19 cm 2 An independent cell device was prepared, thus obtaining a CZTSSe thin film solar cell with a CCO-20 interlayer film inserted.

[0053] The present invention further adjusts the thickness of the intermediate layer film according to the method of the above embodiment, and assembles it into a CZTSSe solar cell for performance testing. The test results are as follows:

[0054] like Figure 1 In order to explore the effect of heat treatment temperature on the valence state of each element on the surface of the film sample, XPS tests were performed on three groups of films. The XPS spectra of Cu and Co elements were obtained as shown in Figure 1 Figures (a)-(c) show the XPS spectra of Cu2p, where Cu2p was detected at 935.5eV and 943eV, respectively. 3 / 2 peak and the corresponding satellite peaks, and the Cu2p 3 / 2 The peaks are fitted into three peaks centered at 932.9 eV, 934.1 eV, and 935.5 eV, which are represented by Cu2O, CuO, and Cu(OH)2, respectively. Figures (d)-(f) show the XPS spectra of Co2p, where Co2p was detected at 780.6 eV and 786.88 eV. 3 / 2 peaks and corresponding satellite peaks, and Co2p 3 / 2 The peaks were fitted into two peaks centered at 780.51 eV and 782.35 eV, which were represented as Co2O3 and CoO, respectively.

[0055] The analysis of elements based on XPS spectrum shows that the heat treatment temperature has an important influence on the Cu 2+ and Cu +The relative content of the two valence states of Cu element is affected by the following formula:

[0056]

[0057]

[0058] Effect of heat treatment temperature on the surface Co of the film 3+ and Co 2+ The relative content of the two valence states of Co element is also affected. The relative content of the two valence states of Co element is calculated according to the following formula:

[0059]

[0060]

[0061] The relative concentrations of Cu and Co in different valence states in the CuCo2O4 film obtained by calculation and analysis are shown in the following table:

[0062]

[0063] Note: There is Cu(OH)2 in the film, so Cu 2+ and Cu + The sum of the percentage values ​​is less than 1, and the difference between the sum of the percentage values ​​and 1 is Cu(OH)2.

[0064] As the heat treatment temperature increases, the Cu 2+ The relative content of Cu ions gradually decreases, while + The relative content of ions gradually increases. 3+ The relative content of ions gradually decreased, while Co 2+ The relative content of ions gradually increases. + ions and Co 2+ The less the relative content of ions, the higher the film conductivity and the higher the carrier concentration. 0.91 2.39CoO 1.35 0.23Cu(OH)2, the compound in CCO-25 is CuO 0.85 2.36CoO 1.33 0.22Cu(OH)2, the compound in CCO-30 is CuO 0.86 2.51CoO 1.20 ·0.30Cu(OH)2.

[0065] like Figure 2As shown in the figure, in order to explore the effect of heat treatment temperature on the electrical properties of CuCo2O4 thin films, Hall tests were performed on three groups of samples at room temperature. The films prepared at all temperatures showed p-type characteristics, and the resistivity of the CuCo2O4 film prepared at 200°C reached 5.0×10 1 Ω·cm, mobility is 3.0×10 -2 cm 2 ·V -1 ·s -1 , and the hole concentration is 4.18×10 18 cm -3 As the temperature rises, the resistivity of the film sample also increases, from 10 1 Increased to 10 2 , the conductivity deteriorates, and the hole concentration and mobility decrease to varying degrees, which is consistent with the XPS results. The resistivity difference of CuCo2O4 films prepared at different temperatures is mainly caused by the hole concentration. Because the mobility difference between the samples is not significant, the higher the hole concentration of the CuCo2O4 film, the smaller the resistivity and the better the conductivity. The Hall test results show that the film prepared at 200°C has the best electrical properties.

[0066] like Figure 3 (a) shows the transmission spectrum of CuCo2O4 films with different heat treatment temperatures tested by UV-visible spectrophotometer at room temperature. In the figure, CCO-20 shows the highest transmittance, with an average transmittance of more than 95%, which is due to its low absorption characteristics in the entire area. The light transmittance of the film samples gradually decreases with the increase of heat treatment temperature. The average transmittance of CCO-30 is 72%, and an absorption edge appears at around 490nm. In addition, the band gap of CuCo2O4 film can be calculated by Tauc formula:

[0067] (αhν) 2 =A(hν-E g )(5)

[0068] where α is the absorption coefficient, hν is the photon energy, A is a constant, and E g is the band gap. From the above formula, we get (αhν) 2 The relationship curve with hν is as follows Figure 3 As shown in (b), when the tangent of the curve intersects the horizontal axis, it is the band gap of the corresponding film sample. It can be observed from the figure that as the heat treatment temperature increases, the band gap of the film gradually decreases, and their band gap values ​​are 3.31eV, 2.36eV ​​and 1.69eV respectively. The optical properties of the CuCo2O4 film prepared in this experiment show the same trend as previously reported.

[0069] in Figure 3 (a) The light transmittance of the main wavelength nodes of each sample is shown in the following table:

[0070]

[0071] like Figure 4 (a) shows the XRD spectra of samples CCO-200 to CCO-203, from which it is found that except for the diffraction peak of metal Mo (2θ=40.52°), the other diffraction peaks are all derived from CZTSSe with kesterite structure. No secondary phase diffraction peaks are observed in the figure, indicating that the introduction of CuCo2O4 intermediate layer does not lead to the generation of new secondary phases in the CZTSSe absorption layer. In addition, it can be seen from the figure that the intensity of the (112) main diffraction peak of CZTSSe first increases and then weakens, among which the diffraction peak intensity of CCO-201 is the strongest, while the diffraction peak intensity of CCO-203 is relatively the weakest. The (112) diffraction peak is enlarged to observe the effect of the intermediate layer on the lattice constant of the CZTSSe absorption layer, as shown in Figure 2. Figure 4 As shown in (b), with the increase of the number of CuCo2O4 spin-coated layers, the (112) diffraction peak gradually moves to a higher diffraction angle, indicating that the relatively small ionic radius of Co 2+ (0.650) enters the absorption layer to replace Zn 2+ (0.740). XRD results show that the four groups of CZTSSe films are all single-phase kesterite structures.

[0072] like Figure 5 As shown, in order to gain a deeper understanding of the effect of the introduction of the CuCo2O4 intermediate layer on the crystal quality of the CZTSSe absorption layer, the half-height width (FWHM) of the main diffraction peak of the four groups of CZTSSe thin films (112) was calculated. The results are shown in the figure, and the half-height width shows a trend of first decreasing and then increasing. According to the Scherrer formula:

[0073]

[0074] Where D is the grain size, K is the Scherrer constant, λ is the wavelength, β is the half-height width of the diffraction peak, and θ is the Bragg diffraction angle. It is calculated that from CCO-200 to CCO-203, the grain size increases first and then decreases. Among them, CCO-201 has the largest grain size and the best crystallinity. As the number of spin-coated CuCo2O4 intermediate layers increases, the crystal quality of the CZTSSe absorption layer decreases.

[0075] like Figure 6 The Raman scattering spectra of samples CCO-200 to CCO-203 are shown in Figure 1. -1 、196cm -1 、234cm -1、247cm -1 and 327cm -1 The vibration peak of CZTSSe appeared at , and no other vibration peaks related to the secondary phase were found. The Raman results further verified that the introduction of the CuCo2O4 intermediate layer did not cause the CZTSSe absorption layer to produce a new secondary phase. Based on the above analysis, the CCO-201 sample has the best properties.

[0076] like Figure 7 As shown, in order to explore the effect of CuCo2O4 interlayer with different heat treatment temperatures on CZTSSe solar cells. CZTSSe solar cells with and without CuCo2O4 interlayer were prepared respectively. Based on the above-mentioned optimal spin coating number of CuCo2O4 interlayer is 1 layer, heat treatment was performed at 200℃, 250℃ and 300℃ for 10min respectively. The samples were named CCO-201, CCO-251 and CCO-301, and a film without CuCo2O4 interlayer was prepared as a reference, named CCO-200. The four groups of film samples were assembled into battery devices, and their JV tests are shown in the figure. It can be seen from the figure that after the introduction of CuCo2O4 interlayer, the PCE of the battery increased from 6.95% to 8.65%. CCO-201 has the highest PCE, which is mainly due to the increase of FF from 51.88% to 61.10% and Jsc from 33.99mA / cm2 to 35.25mA / cm 2 , while Voc does not change much. The significant improvement in FF is due to the improvement in the quality of the back interface, and the increase in Jsc is mainly due to the improvement in the conductivity of the CZTSSe absorption layer. However, as the heat treatment temperature of the CuCo2O4 interlayer increases further, the PCE of the battery begins to decrease. Combined with the analysis of electrical properties, the diode ideal factor A value (1.49) and the reverse saturation current density J0 (9.87×10 -4 ) are the smallest, indicating that the back electrode contact quality is improved and carrier recombination is suppressed. In addition, the smaller series resistance and larger parallel resistance indicate that there is less internal recombination in CCO-201. Therefore, after the CuCo2O4 intermediate layer is assembled into the CZTSSe device, the best battery device is CCO-201.

[0077] The present invention prepares a CuCo2O4 film by a simple sol-gel method, and when the heat treatment temperature of the CuCo2O4 film is 200° C., the film has the best electrical and optical properties. As the heat treatment temperature further increases, the electrical and optical properties deteriorate, and the optical band gap gradually decreases.

[0078] By exploring different spin-coating numbers and heat treatment temperatures of the CuCo2O4 intermediate layer, it was finally found that when the optimal spin-coating number of the CuCo2O4 intermediate layer was 1 layer and the heat treatment temperature was 200°C, the back contact quality of CZTSSe was the best, the crystallinity of the absorption layer was the highest, and the photoelectric conversion efficiency of the solar cell was increased by 24.3% (the photoelectric conversion efficiency increased from 6.95% to 8.65%). On the one hand, this improvement is attributed to the diffusion of part of the Co element from the CuCo2O4 intermediate layer into the absorption layer, replacing the Zn element and suppressing Zn-related defects, thereby improving the quality of the absorption layer; on the other hand, it is because CuCo2O4 as an intermediate layer effectively suppresses the probability of carrier recombination at the back interface, promotes carrier transport, and improves the contact quality of the back electrode. Therefore, a two-way improvement of the CZTSSe absorption layer and the back electrode interface is achieved, ultimately improving the performance of the battery device.

Claims

1. A P-type intermediate layer of a thin-film solar cell, characterized in that: The P-type intermediate layer is a non-crystalline CuCo2O4 layer, which is arranged between the back electrode of the solar cell and the CZTSSe thin film layer. The CuCo2O4 layer has a light transmittance of not less than 60% in the 400-1000nm light wavelength band and a band gap value of not less than 1.5eV.

2. The P-type intermediate layer of the thin-film solar cell according to claim 1, characterized in that: The CuCo2O4 layer has a light transmittance of not less than 80% in the 400-1000nm optical wavelength band, and preferably, a light transmittance of not less than 90%.

3. The P-type intermediate layer of the thin-film solar cell according to claim 1, characterized in that: The band gap value of the CuCo2O4 layer is not less than 2eV, and preferably, has a band gap of not less than 3eV.

4. The P-type intermediate layer of the thin-film solar cell according to claim 1, characterized in that: The thickness of the P-type intermediate layer is 10-100 nm, preferably, the thickness is 10-50 nm, and more preferably, the thickness is 15-20 nm.

5. The P-type intermediate layer of the thin-film solar cell according to claim 1, characterized in that: The amorphous CuCo2O4 layer contains the following compounds: CuO x1 n1CoO x2 ·n2Cu(OH)2, Among them, x1 is 0.80-1.00, x2 is 1.20-1.50, n2 is 0.10-0.40, and n1 / (1+n2) is 1.90-2.10; Preferably, x1 is 0.85 to 0.95, x2 is 1.30 to 1.40, n2 is 0.15 to 0.30, and n1 / (1+n2) is 1.90 to 2.00; More preferably, x1 is 0.90 to 0.95, x2 is 1.33 to 1.36, and n2 is 0.20 to 0.

25.

6. The P-type intermediate layer of the thin-film solar cell according to claim 1, characterized in that: The CuCo2O4 intermediate layer is prepared by a sol-gel method. 2+ and Cu 2+ The mixed solution prepared by coating and heat treating with organic acid salt or its crystal water compound is obtained, wherein Co 2+ and Cu 2+ The molar ratio is 1.9 to 2.1:

1.

7. The P-type intermediate layer of the thin-film solar cell according to claim 6, characterized in that: The concentration of the mixed solution is 0.1-0.5M, and the CuCo2O4 intermediate layer is obtained by coating a single layer of the mixed solution and performing heat treatment.

8. The P-type intermediate layer of the thin-film solar cell according to claim 6, characterized in that: The heat treatment temperature is 180-350° C., preferably 180-250° C., more preferably 200-220° C., and the heat treatment time is 5-15 minutes.

9. Use of the P-type intermediate layer of the thin-film solar cell according to any one of claims 1 to 8 in the preparation of solar thin-film cells.

10. A method for preparing a solar thin film battery comprising a P-type intermediate layer according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1. Solution preparation and processing, including 2+ and Cu 2+ An organic acid salt or a hydrate of crystals thereof is used to prepare a mixed solution; Step 2. Preparation and treatment of a back electrode, including using soda-lime glass as a substrate and sputtering a Mo layer on the substrate as a back electrode of a CZTSSe solar cell; Step 3. Prepare a CZTSSe absorption layer film inserted into the CuCo2O4 layer, including applying the mixed solution obtained in step 1 on the back electrode and performing heat treatment to obtain a CuCo2O4 layer, then applying a CZTS precursor solution on the CuCo2O4 layer, and further performing selenization treatment to obtain a CZTSSe absorption layer film inserted into the CuCo2O4 layer; Step 4. preparing a solar cell, including depositing a cadmium sulfide (CdS) film on the absorption layer film obtained in step 3 by a chemical water bath method, further depositing high-resistance intrinsic zinc oxide (i-ZnO) and low-resistance indium tin oxide (ITO) to form a window layer of a CZTSSe solar cell, and further evaporating Ag on the surface of the thin film of the window layer as a top electrode to obtain a solar cell; Wherein, the CuCo2O4 layer in step 3 is a CuCo2O4 layer obtained by coating and heat treating the mixed solution at least once.